A ternary positive electrode fiber composite material and preparation method thereof

The ternary positive electrode fiber precursor was constructed by coaxial electrospinning method and a nitrogen-containing polymer clad layer was introduced, which solved the problem of insufficient heat resistance and rate performance of the ternary positive electrode material, and achieved high conductivity and excellent electrochemical performance.

CN115332508BActive Publication Date: 2025-03-25GUANGDONG BRUNP RECYCLING TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211009305.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-19
Publication Date
2025-03-25
Estimated Expiration
2042-08-19

AI Technical Summary

Technical Problem

The existing ternary cathode materials cannot meet the needs of diverse use scenarios due to poor heat resistance, short service life and poor rate performance.

Method used

A coaxial fiber precursor with a sandwich structure is pre-constructed by coaxial electrospinning method, and a nitrogen-containing polymer cladding layer is introduced through a monomer polymer grafting method, and a ternary positive electrode carbon composite material is formed by sintering at high temperature.

Benefits of technology

It effectively improves the conductivity and electrochemical properties of the material, retains the fiber network structure and morphology, and improves service life and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003806544330000101
    Figure BDA0003806544330000101
  • Figure BDA0003806544330000111
    Figure BDA0003806544330000111
  • Figure HDA0003806544340000011
    Figure HDA0003806544340000011
Patent Text Reader

Abstract

The present invention discloses a ternary positive electrode fiber composite material and a preparation method thereof, which belongs to the field of battery materials. The preparation method of the ternary positive electrode fiber composite material of the present invention pre-constructs a coaxial fiber precursor with a sandwich structure by a coaxial electrospinning method, and then introduces a nitrogen-containing polymer coating layer to coat the fiber surface by a monomer polymer grafting method, and after high-temperature sintering, the two-layer structure in the fiber precursor is fused to form a ternary positive electrode carbon composite material, and the outer nitrogen-containing coating layer is converted into a nitrogen-containing carbon layer to effectively retain the fiber morphology, while effectively improving the conductivity of the overall material. The present invention also discloses a lithium-ion battery positive electrode sheet prepared from the ternary positive electrode fiber composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery materials, and in particular to a ternary positive electrode fiber composite material and a preparation method thereof. Background Art

[0002] Ternary cathode materials are nickel-cobalt-manganese-oxide lithium materials prepared by adjusting the proportions of nickel, manganese and cobalt sources according to actual needs. This material has the advantages of low cost, high unit capacity and good safety. However, with the diversification of usage scenarios, pure ternary cathode materials can no longer meet the needs of all users due to their poor heat resistance, short service life and poor rate performance.

[0003] Based on the inherent defects of pure ternary positive electrode materials, people have begun to use some modification methods for optimization, mainly including element doping and structural modification. Structural modification of ternary positive electrode materials, especially giving the materials a special morphology, can effectively improve the thermal stability and electrochemical properties of the materials through physical means alone.

[0004] In the prior art, electrospinning is a commonly used modification and structural construction method for lithium-ion battery materials. This method mainly uses high-voltage static electricity to accelerate the charged material under the action of the electric field force and overcome the surface tension to form a jet stream. The solvent evaporates or solidifies during the jetting process, and finally falls on the receiving device to form a non-woven fiber felt. This three-dimensional fiber composite structure can effectively improve the structural force performance of the product, and at the same time, the specific surface area is significantly larger, making it easier to infiltrate the electrolyte, and the lithium deintercalation sites will also increase, effectively improving the overall electrochemical activity of the material. However, since the electrospinning process is time-consuming, the raw materials containing the solid-liquid phase are prone to static stratification and block the needle during the spinning process. Therefore, the existing electrospinning raw materials are mostly pure liquid phases. For ternary positive electrode materials, although soluble salts can be used as raw materials for electrospinning morphology construction, these precursor raw materials will undergo obvious crystallization behavior during the subsequent sintering process, resulting in internal shrinkage and eventual breakage and damage of the previously constructed fiber morphology. Summary of the invention

[0005] Based on the deficiencies of the prior art, the purpose of the present invention is to provide a method for preparing a ternary positive electrode fiber composite material. This method pre-constructs a coaxial fiber precursor with a sandwich structure through a coaxial electrospinning method, and then introduces a nitrogen-containing polymer coating layer to coat the fiber surface through a monomer polymer grafting method. After high-temperature sintering, the two-layer structure in the fiber precursor is fused to form a ternary positive electrode carbon composite material, and the outer nitrogen-containing coating layer is converted into a nitrogen-containing carbon layer to effectively retain the fiber morphology, while effectively improving the conductivity of the overall material.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing a ternary positive electrode fiber composite material comprises the following steps:

[0008] (1) dissolving a cobalt source, a nickel source, a manganese source and a structural polymer in solution A to prepare a spinning solution I, and dissolving a lithium source and a structural polymer in solution A to prepare a spinning solution II;

[0009] (2) using spinning solution I as the inner axis spinning solution and spinning solution II as the outer axis spinning solution, electrospinning is performed using a coaxial structure needle, and the obtained fiber cloth is dried to obtain a coaxial fiber precursor a;

[0010] (3) dissolving the nitrogen-containing polymerizable monomer in solution B, then placing the coaxial fiber precursor a in the solution to completely immerse it, adding a catalyst to initiate a polymerization reaction of the nitrogen-containing polymerizable monomer, filtering and drying after the reaction is complete, to obtain a coaxial fiber precursor b; the cobalt source, nickel source, manganese source, lithium source and structural polymer are insoluble in solution B;

[0011] (4) The coaxial fiber precursor b is calcined at 700-900° C. for 10-15 h under a protective atmosphere to obtain the ternary positive electrode fiber composite material.

[0012] The preparation method of the ternary positive electrode fiber composite material of the present invention adopts a coaxial electrostatic spinning method to prepare a coaxial fiber precursor with a cobalt source, a nickel source and a manganese source as an inner axis and a lithium source as an outer axis, and both the inner and outer axes are fixed in shape with a structural polymer. Subsequently, the precursor further introduces a nitrogen-containing polymer monomer, and a thin layer of nitrogen-containing polymer is grafted on the surface of the precursor using the structural polymer contained in the precursor as a grafting site. When the precursor is sintered at a high temperature to generate nickel cobalt manganese oxide, the cobalt source, nickel source and manganese source of the inner axis and the lithium source of the outer axis crystallize, but because the two are in different structural positions, the stress trend is opposite, the overall internal shrinkage stress is significantly reduced, the inner and outer axes fuse, and the nitrogen-containing polymer grafted on the outer layer is carbonized into a nitrogen-containing carbon layer with high conductivity during high-temperature sintering, and the coaxial fiber is effectively pulled to help it maintain its morphology. The ternary positive electrode fiber composite material finally prepared not only has high conductivity, but also retains a relatively complete fiber network structure, has a large specific surface area, is rich in lithium deintercalation sites, has a high proportion of active ternary materials, and has excellent electrochemical properties.

[0013] Preferably, the cobalt source, nickel source and manganese source are soluble salts; the lithium source is lithium carbonate, the structural polymer is polyimide, and the solution A is N,N-dimethylformamide (DMF).

[0014] More preferably, the cobalt source is at least one of cobalt acetate and cobalt nitrate, the nickel source is at least one of nickel acetate and nickel nitrate, and the manganese source is manganese acetate.

[0015] It should be particularly noted that, in addition to the preferred types described above, the cobalt source, nickel source, manganese source and lithium source of the present invention may also be other soluble salts that are soluble in solution A, as long as they can be configured into a solution for electrospinning and can subsequently be directly synthesized into nickel cobalt manganese oxide, they are not limited to the above preferred range.

[0016] Preferably, the molar ratio of the cobalt element in the cobalt source, the nickel element in the nickel source and the manganese element in the manganese source is x:y:(1-xy), wherein x=0.01-0.1.

[0017] Preferably, the mass concentration of the structural polymer in the spinning solution I and the spinning solution II is 5wt% to 15wt%, the total concentration of cobalt ions, nickel ions and manganese ions in the spinning solution I is 0.4 to 0.8 mmol / g, and the concentration of lithium ions in the spinning solution II is 0.4 to 0.8 mmol / g.

[0018] In the electrospinning process, the introduction of structural polymers not only helps the spinning shaping and continuous spinning, but also serves as a carrier for raw materials such as cobalt source and lithium source in the obtained coaxial fiber precursor a. If the content is too little, various raw material solutions are prone to loss during subsequent processing, and nitrogen-containing polymerization monomers cannot be fully grafted and polymerized. If the content is too much, the spinning solution is too viscous, which can easily affect the spinning effect and may also affect the subsequent crystallization synthesis efficiency of nickel cobalt manganese oxide.

[0019] Preferably, during the electrospinning treatment in step (2), the inner diameter of the needle used for the outer axis spinning is 0.8-1.5 mm, the inner diameter of the needle used for the inner axis spinning is 0.3-0.5 mm, the injection rate is 0.4-0.6 mL / h, the voltage is set to 18-22 kV, and the spinning receiving distance is 10-25 cm.

[0020] Preferably, the nitrogen-containing polymerizable monomer is pyrrole, the catalyst is ferric chloride, and the solution B is anhydrous ethanol.

[0021] Preferably, the mass ratio of the structural polymer to the nitrogen-containing polymerizable monomer in the coaxial fiber precursor a is 1:(0.2-0.4).

[0022] If too much nitrogen-containing polymerization monomer is introduced, although more polypyrrole can be formed during the polymerization process, not all of it can be grafted onto the coaxial fiber precursor a, which has limited improvement in the stability of the final product and may also cause uneven distribution of active substances in the overall product. If too little is introduced, it will be difficult to effectively exert the traction effect and ensure the fiber morphology of the final product. At the same time, the nitrogen doping amount is insufficient, and the conductivity of the product is insufficiently improved.

[0023] Preferably, the polymerization reaction in step (3) is carried out at -5 to 5°C.

[0024] Another object of the present invention is to provide a ternary positive electrode fiber composite material prepared by the preparation method of the ternary positive electrode fiber composite material.

[0025] Another object of the present invention is to provide a lithium-ion battery positive electrode plate, which is prepared from the ternary positive electrode fiber composite material of the present invention.

[0026] The ternary positive electrode fiber composite material of the present invention has an excellent three-dimensional fiber structure, a large specific surface area, and many lithium insertion and extraction sites. It also contains nitrogen doping. When used in the positive electrode of a lithium-ion battery, it not only has good lithium insertion and extraction efficiency and high conductivity, but also has good cycle stability and a service life that is improved compared to existing products.

[0027] The beneficial effect of the present invention is that the present invention provides a method for preparing a ternary positive electrode fiber composite material, which pre-constructs a coaxial fiber precursor with a sandwich structure by a coaxial electrospinning method, and then introduces a nitrogen-containing polymer coating layer to coat the fiber surface by a monomer polymer grafting method, and after high-temperature sintering, the two-layer structure in the fiber precursor is fused to form a ternary positive electrode carbon composite material, and the outer nitrogen-containing coating layer is converted into a nitrogen-containing carbon layer to effectively retain the fiber morphology and effectively improve the conductivity of the overall material. The present invention also provides a lithium-ion battery positive electrode sheet prepared from the ternary positive electrode fiber composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a transmission electron microscope image of the ternary positive electrode fiber composite material obtained in Example 1 of the present invention.

[0029] Figure 2 This is a transmission electron microscope image of the ternary positive electrode fiber composite material obtained in Comparative Example 1 of the present invention.

[0030] Figure 3 This is a transmission electron microscope image of the ternary positive electrode fiber composite material obtained in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0031] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents, raw materials and instruments designed for the implementation of the present invention and comparative examples are all commonly used ordinary reagents, raw materials and instruments unless otherwise specified.

[0032] Preferably, the polyimide used in each embodiment and comparative example can be selected from matrimid 5218PI powder, and the molar ratio of the cobalt element in the cobalt source, the nickel element in the nickel source and the manganese element in the manganese source is 0.1:0.8:0.1. It should be noted that the embodiments and comparative examples of the present invention are only described by some specific feasible schemes, but are not limited thereto. Those skilled in the art should know that without affecting the feasibility of the overall technical scheme, the polyimide can be selected from other sources, and the molar ratio of the three elements of nickel, cobalt and manganese in the product can be adjusted according to actual needs.

[0033] Example 1

[0034] An embodiment of the ternary positive electrode fiber composite material and a preparation method thereof according to the present invention comprises the following steps:

[0035] (1) Cobalt acetate as a cobalt source, nickel acetate as a nickel source, manganese acetate as a manganese source, and 10 wt% of a structural polymer polyimide by weight of the total solution are dissolved in DMF under stirring at 60-80° C. in a water bath to prepare a spinning solution I; lithium acetate as a lithium source and 10 wt% of a structural polymer polyimide by weight of the total solution are dissolved in DMF under stirring at 60-80° C. in a water bath to prepare a spinning solution II; the molar ratio of the cobalt element in the cobalt source, the nickel element in the nickel source, and the manganese element in the manganese source is x:y:(1-xy), wherein x=0.1 and y=0.8; the total concentration of the three ions of cobalt ion, nickel ion, and manganese ion in the spinning solution I is 0.6 mmol / g; the concentration of lithium ion in the spinning solution II is 0.6 mmol / g;

[0036] (2) Using spinning solution I as the inner axis spinning solution and spinning solution II as the outer axis spinning solution, electrospinning was performed using a coaxial structure needle. The obtained fiber cloth was dried at 80° C. for 24 h to obtain a coaxial fiber precursor a. The specific parameters used were: the inner diameter of the needle used for the outer axis spinning was 1.2 mm, the inner diameter of the needle used for the inner axis spinning was 0.3 mm, the injection rate was 0.5 mL / h, the voltage was set to 19 kV, and the spinning receiving distance was 22 cm.

[0037] (3) Dissolving the nitrogen-containing polymer monomer pyrrole in anhydrous ethanol, then placing the coaxial fiber precursor a in the solution to completely immerse, adjusting the solution temperature to lower to 0°C, adding an appropriate amount of ferric chloride to initiate the polymerization reaction of the nitrogen-containing polymer monomer pyrrole, filtering after the reaction is complete and drying at 60°C for 24 hours to obtain the coaxial fiber precursor b; wherein the amount of pyrrole added is: the total added mass of polyimide: the added mass of pyrrole = 1:0.3;

[0038] (4) The coaxial fiber precursor b is calcined at 850° C. for 15 h under a protective atmosphere to obtain the ternary positive electrode fiber composite material.

[0039] Example 2

[0040] An embodiment of the ternary positive electrode fiber composite material and the preparation method thereof according to the present invention, the difference between this embodiment and embodiment 1 is that the mass concentration of polyimide in the spinning solution I and the spinning solution II in the step (1) is 15wt%, the total concentration of cobalt ions, nickel ions and manganese ions in the spinning solution I is 0.4mmol / g, and the concentration of lithium ions in the spinning solution II is 0.4mmol / g.

[0041] Example 3

[0042] An embodiment of the ternary positive electrode fiber composite material and the preparation method thereof according to the present invention, the difference between this embodiment and embodiment 1 is that the mass concentration of polyimide in the spinning solution I and the spinning solution II in the step (1) is 5wt%, the total concentration of cobalt ions, nickel ions and manganese ions in the spinning solution I is 0.8mmol / g, and the concentration of lithium ions in the spinning solution II is 0.8mmol / g.

[0043] Example 4

[0044] An embodiment of the ternary positive electrode fiber composite material and the preparation method thereof according to the present invention, the difference between this embodiment and embodiment 1 is that the mass concentration of polyimide in the spinning solution I and the spinning solution II in the step (1) is 20wt%, the total concentration of cobalt ions, nickel ions and manganese ions in the spinning solution I is 0.2mmol / g, and the concentration of lithium ions in the spinning solution II is 0.2mmol / g.

[0045] Example 5

[0046] An embodiment of the ternary positive electrode fiber composite material and the preparation method thereof according to the present invention, the difference between this embodiment and embodiment 1 is that the mass concentration of polyimide in the spinning solution I and the spinning solution II in the step (1) is 3wt%, the total concentration of cobalt ions, nickel ions and manganese ions in the spinning solution I is 1mmol / g, and the concentration of lithium ions in the spinning solution II is 1mmol / g.

[0047] Example 6

[0048] An embodiment of the ternary positive electrode fiber composite material and the preparation method thereof of the present invention, the difference between this embodiment and embodiment 1 is only that the amount of pyrrole added in step (3) is: total added mass of polyimide: added mass of pyrrole = 1:0.2.

[0049] Example 7

[0050] An embodiment of the ternary positive electrode fiber composite material and the preparation method thereof of the present invention, the difference between this embodiment and embodiment 1 is only that the amount of pyrrole added in step (3) is: total added mass of polyimide: added mass of pyrrole = 1:0.4.

[0051] Example 8

[0052] An embodiment of the ternary positive electrode fiber composite material and the preparation method thereof of the present invention, the difference between this embodiment and embodiment 1 is only that the amount of pyrrole added in step (3) is: total added mass of polyimide: added mass of pyrrole = 1:0.1.

[0053] Example 9

[0054] An embodiment of the ternary positive electrode fiber composite material and the preparation method thereof of the present invention, the difference between this embodiment and embodiment 1 is only that the amount of pyrrole added in step (3) is: total added mass of polyimide: added mass of pyrrole = 1:0.5.

[0055] Comparative Example 1

[0056] A ternary positive electrode fiber composite material and a preparation method thereof, comprising the following steps:

[0057] (1) lithium acetate as a lithium source, cobalt acetate as a cobalt source, nickel acetate as a nickel source, manganese acetate as a manganese source, and 20 wt% of a structural polymer polyimide accounting for the total solution mass are dissolved in DMF under stirring at 60-80° C. in a water bath to prepare a spinning solution, wherein the molar ratio of the cobalt element in the cobalt source, the nickel element in the nickel source, and the manganese element in the manganese source is x:y:(1-xy), wherein x=0.1, y=0.8; the total concentration of the three ions of cobalt ion, nickel ion, and manganese ion in the spinning solution is 0.6 mmol / g; and the concentration of the lithium ion is 0.6 mmol / g;

[0058] (2) The spinning solution was subjected to electrospinning treatment, and the obtained fiber cloth was dried at 80° C. for 24 h to obtain a fiber precursor a; wherein the specific parameters used were: the inner diameter of the needle used for spinning, the injection rate was 0.3 mL / h, the voltage was set to 20 kV, and the spinning receiving distance was 22 cm;

[0059] (3) Dissolving the nitrogen-containing polymer monomer pyrrole in anhydrous ethanol, then placing the fiber precursor a in the solution and completely immersing it, adjusting the solution temperature to 0°C, adding an appropriate amount of ferric chloride to initiate the polymerization reaction of the nitrogen-containing polymer monomer pyrrole, filtering after the reaction is complete and drying at 60°C for 24 hours to obtain a coaxial fiber precursor b; wherein the amount of pyrrole added is: polyimide added mass: pyrrole added mass = 1:0.3;

[0060] (4) The coaxial fiber precursor b is calcined at 850° C. for 15 h under a protective atmosphere to obtain the ternary positive electrode fiber composite material.

[0061] Comparative Example 2

[0062] A ternary positive electrode fiber composite material and a preparation method thereof, comprising the following steps:

[0063] (1) Cobalt acetate as a cobalt source, nickel acetate as a nickel source, manganese acetate as a manganese source, and 10 wt% of a structural polymer polyimide by weight of the total solution are dissolved in DMF under stirring at 60-80° C. in a water bath to prepare a spinning solution I; lithium acetate as a lithium source and 10 wt% of a structural polymer polyimide by weight of the total solution are dissolved in DMF under stirring at 60-80° C. in a water bath to prepare a spinning solution II; the molar ratio of the cobalt element in the cobalt source, the nickel element in the nickel source, and the manganese element in the manganese source is x:y:(1-xy), wherein x=0.1 and y=0.8; the total concentration of the three ions of cobalt ion, nickel ion, and manganese ion in the spinning solution I is 0.6 mmol / g; the concentration of lithium ion in the spinning solution II is 0.6 mmol / g;

[0064] (2) Using spinning solution I as the inner axis spinning solution and spinning solution II as the outer axis spinning solution, electrospinning was performed using a coaxial structure needle. The obtained fiber cloth was dried at 80° C. for 24 h to obtain a coaxial fiber precursor a. The specific parameters used were: the inner diameter of the needle used for the outer axis spinning was 1.2 mm, the inner diameter of the needle used for the inner axis spinning was 0.3 mm, the injection rate was 0.5 mL / h, the voltage was set to 19 kV, and the spinning receiving distance was 22 cm.

[0065] (3) The coaxial fiber precursor a is calcined at 850° C. for 15 h under a protective atmosphere to obtain the ternary positive electrode fiber composite material.

[0066] Comparative Example 3

[0067] A ternary positive electrode fiber composite material and a preparation method thereof, comprising the following steps:

[0068] (1) Cobalt acetate as a cobalt source, nickel acetate as a nickel source, manganese acetate as a manganese source, and 10 wt% of a structural polymer polyimide by weight of the total solution are dissolved in DMF under stirring at 60-80° C. in a water bath to prepare a spinning solution I; lithium acetate as a lithium source and 10 wt% of a structural polymer polyimide by weight of the total solution are dissolved in DMF under stirring at 60-80° C. in a water bath to prepare a spinning solution II; the molar ratio of the cobalt element in the cobalt source, the nickel element in the nickel source, and the manganese element in the manganese source is x:y:(1-xy), wherein x=0.1 and y=0.8; the total concentration of the three ions of cobalt ion, nickel ion, and manganese ion in the spinning solution I is 0.6 mmol / g; the concentration of lithium ion in the spinning solution II is 0.6 mmol / g;

[0069] (2) Using spinning solution I as the inner axis spinning solution and spinning solution II as the outer axis spinning solution, electrospinning was performed using a coaxial structure needle. The obtained fiber cloth was dried at 80° C. for 24 h to obtain a coaxial fiber precursor a. The specific parameters used were: the inner diameter of the needle used for the outer axis spinning was 1.2 mm, the inner diameter of the needle used for the inner axis spinning was 0.3 mm, the injection rate was 0.5 mL / h, the voltage was set to 19 kV, and the spinning receiving distance was 22 cm.

[0070] (3) The reduced graphene oxide rGO prepared by the HUMMER method was placed in anhydrous ethanol, and then the coaxial fiber precursor a was placed in the solution and completely immersed, and the rGO and the coaxial fiber precursor a were stirred at a rate of 50 rpm in an ultrasonic environment to mix evenly, filtered and placed in an environment of 60°C to dry for 24 hours to obtain the coaxial fiber precursor b; wherein the amount of pyrrole added is: the total added mass of polyimide: the added mass of pyrrole = 1:0.3;

[0071] (4) The coaxial fiber precursor b is calcined at 850° C. for 15 h under a protective atmosphere to obtain the ternary positive electrode fiber composite material.

[0072] Effect Example 1

[0073] In order to verify the preferredness of the preparation methods of the ternary positive electrode fiber composite materials of the present invention, the products of Example 1, Comparative Example 1 and Comparative Example 2 were observed by transmission electron microscopy. The test results are as follows: Figures 1 to 3 As shown, it can be seen that under the preferred preparation method of the present invention, the obtained product has good fiber morphology, and the overall fiber structure does not collapse due to the action of the two polymers during the sintering process of the ternary positive electrode material; in contrast, the coaxial spinning process is not used in the preparation process of the comparative example 1 product, and the pre-constructed fiber morphology of the ternary positive electrode material is destroyed during the sintering and crystallization process, and the comparative example 2 product has no outer layer of nitrogen-containing polymer coating, so it is also difficult to maintain a good three-dimensional fiber network structure during high-temperature sintering, and there is obvious fiber breakage after sintering.

[0074] Effect Example 2

[0075] In order to verify the performance preference of each ternary positive electrode fiber composite material of the present invention, each embodiment and comparative example product is used to prepare a positive electrode plate of a lithium-ion battery: each embodiment and comparative example product is mixed with carbon black and PVDF in a mass ratio of 8:1:1 and stirred to prepare a slurry, and then coated on an aluminum foil and cut to prepare a plate.

[0076] The obtained electrode was used as the positive electrode, the lithium sheet was used as the counter electrode, and a button-type lithium-ion half-cell was prepared using a commercial diaphragm and a commercial lithium hexafluorophosphate electrolyte. The obtained battery was cycled for 100 times at a working voltage of 3-4.5V and a rate of 0.1C. At the same time, another batch of samples was prepared in parallel for rate performance testing: first cycled for 10 times at a rate of 0.1C at the same voltage, then cycled for 50 times at a high rate of 2C, and then returned to the rate of 0.1C to calculate the capacity retention rate. The test results are shown in Table 1.

[0077] Table 1

[0078]

[0079]

[0080] As can be seen from Table 1, due to the coaxial spinning treatment of the precursor during the preparation process, and the stabilizing effect of the structural polymer and the conductive polymer, the lithium nickel cobalt manganese oxide in the material can be crystallized in situ during the sintering synthesis process, which will not have much impact on the fiber structure of the product. The overall product has a large specific surface area, presents a good three-dimensional fiber structure, has high stability and many lithium deintercalation sites, and can effectively infiltrate the electrolyte; at the same time, in the case of nitrogen doping, the conductivity of the product is improved. When used in a low-rate cycle process, the initial discharge specific capacity of the obtained ternary positive fiber composite material can reach 160-185mAh / g, and the discharge ratio after 100 cycles can also easily reach 140-165%, and the capacity retention rate after the rate test can reach up to 92%. It can be seen from the comparison between Example 1 and Example 2-9 that whether the addition ratio of the structural polymer, the conductive polymer (i.e., polypyrrole) or the ternary material changes, the discharge capacity, cycle stability and rate performance of the final product will change, so it needs to be maintained in a good range. In contrast, the product of Comparative Example 1 does not use the coaxial spinning method to prepare the precursor. After the subsequent loading and sintering steps, the product is difficult to maintain the pre-constructed fiber structure, and the product's cycle stability and rate performance are poor; although the product of Comparative Example 2 uses the coaxial spinning method to prepare the precursor, it does not further introduce an outer nitrogen-containing polymer coating layer, and the morphology and structure of the final product are also not ideal. At the same time, due to the lack of nitrogen doping, the product has insufficient conductivity and a low discharge specific capacity; the product of Comparative Example 3 uses common carbon-modified material reduced graphene instead of the polypyrrole coating in the embodiment during the preparation process, but it is difficult to combine the reduced graphene to the precursor by simple physical dispersion. Therefore, although the comprehensive performance of the product is improved compared with the product of Comparative Example 2, the overall effect is still not as good as the product of the embodiment.

[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a ternary positive electrode fiber composite material, characterized in that: The following steps are involved: (1) dissolving a cobalt source, a nickel source, a manganese source and a structural polymer in solution A to prepare a spinning solution I, and dissolving a lithium source and a structural polymer in solution A to prepare a spinning solution II; (2) using spinning solution I as the inner axis spinning solution and spinning solution II as the outer axis spinning solution, electrospinning is performed using a coaxial structure needle, and the obtained fiber cloth is dried to obtain a coaxial fiber precursor a; (3) dissolving the nitrogen-containing polymerizable monomer in solution B, then placing the coaxial fiber precursor a in the solution to completely immerse it, adding a catalyst to initiate a polymerization reaction of the nitrogen-containing polymerizable monomer, filtering and drying after the reaction is complete, to obtain a coaxial fiber precursor b; the cobalt source, nickel source, manganese source, lithium source and structural polymer are insoluble in solution B; (4) The coaxial fiber precursor b is calcined at 700-900° C. for 10-15 h under a protective atmosphere to obtain the ternary positive electrode fiber composite material.

2. The method for preparing the ternary positive electrode fiber composite material according to claim 1, characterized in that: The cobalt source, nickel source and manganese source are soluble salts; the lithium source is lithium carbonate, the structural polymer is polyimide, and the solution A is N,N-dimethylformamide.

3. The method for preparing the ternary positive electrode fiber composite material according to claim 2, characterized in that: The cobalt source is at least one of cobalt acetate and cobalt nitrate, the nickel source is at least one of nickel acetate and nickel nitrate, and the manganese source is manganese acetate.

4. The method for preparing the ternary positive electrode fiber composite material according to claim 3, characterized in that: The molar ratio of the cobalt element in the cobalt source, the nickel element in the nickel source and the manganese element in the manganese source is x:y:(1-xy), wherein x=0.01-0.

1.

5. The method for preparing the ternary positive electrode fiber composite material according to claim 1, characterized in that: The mass concentration of the structural polymer in the spinning solution I and the spinning solution II is 5wt% to 15wt%, the total concentration of cobalt ions, nickel ions and manganese ions in the spinning solution I is 0.4 to 0.8mmol / g, and the concentration of lithium ions in the spinning solution II is 0.4 to 0.8mmol / g.

6. The method for preparing the ternary positive electrode fiber composite material according to claim 1, characterized in that: During the electrospinning treatment in step (2), the inner diameter of the needle used for the outer axis spinning is 0.8-1.5 mm, the inner diameter of the needle used for the inner axis spinning is 0.3-0.5 mm, the injection rate is 0.4-0.6 mL / h, the voltage is set to 18-22 kV, and the spinning receiving distance is 10-25 cm.

7. The method for preparing the ternary positive electrode fiber composite material according to claim 1, characterized in that: The nitrogen-containing polymer monomer is pyrrole, the catalyst is ferric chloride, and the solution B is anhydrous ethanol.

8. The method for preparing the ternary positive electrode fiber composite material according to claim 1, characterized in that: The mass ratio of the structural polymer to the nitrogen-containing polymer monomer in the coaxial fiber precursor a is 1:(0.2-0.4). 9 . The ternary positive electrode fiber composite material prepared by the method for preparing the ternary positive electrode fiber composite material according to any one of claims 1 to 8 .

10. A positive electrode plate for a lithium ion battery, characterized in that: Prepared from the ternary positive electrode fiber composite material as described in claim 9.

Citation Information

Patent Citations

  • Method for preparing high-nickel ternary lithium battery positive-pole material with nickel-lithium mixed discharge inhibited by fiber

    CN108511747A

  • Preparation method of hollow tubular lithium-rich manganese-based positive electrode material

    CN108574089A